Intersecting Voices: Gender, Religion, and Language Practices among University Students in Eastern Indonesia - Afdhal, Afdhal (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2023)
Language functions not merely as a means of communication but as a social arena where gender and religious identities are continuously negotiated and redefined. This study analyzes how language practices among students at Pattimura University reflect and construct social ideologies related to gender and religion within academic and everyday interactions. Using a Critical Discourse Analysis (CDA) approach within a sociocultural linguistics framework, data were collected through classroom observations, informal conversations in campus public spaces, social media interactions, and in-depth interviews. The analysis followed three stages: textual analysis, discursive practice analysis, and social practice analysis. Findings reveal that address terms and religious expressions, such as “abang/babang” and “bung/bu” for male students, “caca” and “ussy” for female students, and faith-based utterances in daily interactions, serve as linguistic markers of intercommunity identity. These practices demonstrate linguistic accommodation as a strategy for maintaining social harmony while preserving symbolic boundaries between groups. Moreover, gendered positioning emerges as male students often dominate conversational spaces, whereas female students negotiate social positioning through more subtle discursive strategies. The study’s novelty lies in introducing the concept of Interfaith Gendered Discourse, which highlights the simultaneous intersection of gender and religion in linguistic practice. It calls for strengthening critical cross-identity literacy in higher education and expanding sociolinguistic inquiry into multicultural contexts of Eastern Indonesia.